Estrategias didácticas que motiven la participación de los estudiantes y la consecuente mejora de su rendimiento académico. Año lectivo 2022-2023 - Santorun Cumbicus, Brayan Alberto (2023)
In this curricular integration work, the importance of the implementation of didactic strategies is strengthened, from a constructivist approach, in the teaching and learning process of Biology. Through these strategies it is possible to motivate the active participation of students. The proposed objective was: <<To enhance the academic performance of students through the implementation of constructivist didactic strategies, which motivate their active participation in the teaching and learning process of Biology in the first year of baccalaureate in “Pio Jaramillo Alvarado” educative unit, during the academic period 2022 – 2023>>. The methodology corresponds to the inductive method with a qualitative approach, thus, the more representative characteristics around the identified problems were determined, which were affecting the academic performance of students. In this way, this allowed to propose an intervention proposal to provide solution to the reality that was affecting the academic performance of students. On the other hand, the work is participative action research, because, since the proposal of the problem and intervention development, where would be an active student’s participation (object of study), both with the researcher with the aim to improve the identified reality. According to the temporality, it corresponds to transversal type, because, it was made in a relatively short period of time. Finally, the obtained results, determine that the constructivist didactic strategies implemented in the TLP of Biology, had a high grade of efficacy, at the moment of motivate the active participation of students, which reflects in the significative improvement of their grades, after the development of the intervention proposal. Keywords: Constructivists didactic strategies, academic performance, teaching and learning , active participation.